On the Study of Chemostat Model with Pulsed Input in a Polluted Environment - Zhong Zhao; Xinyu Song (Discrete Dynamics in Nature and Society)
Chemostat model with pulsed input in a polluted environment is considered. By using the Floquet theorem, we find that the microorganism eradication periodic solution is globally asymptotically stable if the impulsive period T is more than a critical value. At the same time, we can find that the nutrient and microorganism are permanent if the impulsive period T is less than the critical value.